2020
DOI: 10.1177/1056789520954475
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different compositions of fiber metal laminates on the fracture in the semi-solidified stamping forming

Abstract: Fiber metal laminates (FMLs) are widely used in manufacturing due to the high specific strength, fatigue resistance, and lightweight. However, because of the deformation coordination of different layers of FMLs, challenges have been faced in rapid and small part forming. To research the feasibility of the fast forming of small parts using the FMLs, the influence of different compositions of FMLs on the stamping performance under the semi-solidified process condition was investigated, including the outer alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It is worth mentioning that s i ðhÞ should be zero when h ¼ p 2 , because there is no relative movement of tendency of any layer at the polar point. Several studies have demonstrated the accuracy of Coulomb model both in cured and semi-cured numerical simulations (Blala et al, 2019;Li et al, 2020aLi et al, , 2020b. With the help of shear stress distribution law of general adhesion structure, it may be assumed that the distribution of s i ðhÞ along h presents the characteristics of cosine function, and this assumption can effectively decrease the difficulty of solving equation ( 12).…”
Section: Theoretical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that s i ðhÞ should be zero when h ¼ p 2 , because there is no relative movement of tendency of any layer at the polar point. Several studies have demonstrated the accuracy of Coulomb model both in cured and semi-cured numerical simulations (Blala et al, 2019;Li et al, 2020aLi et al, , 2020b. With the help of shear stress distribution law of general adhesion structure, it may be assumed that the distribution of s i ðhÞ along h presents the characteristics of cosine function, and this assumption can effectively decrease the difficulty of solving equation ( 12).…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The metal layers were manufactured using multilayer sheet hydroforming to improve the efficiency, while the prepreg was laid in the middle of FMLs curing of the part. To our best knowledge, the semi-cured FMLs has better formability than the cured one since the semi-cured resin allows large slip at the interface (Li et al, 2020a;Sherkatghanad et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a successful type of Fiber Metal Laminates (FMLs), GLARE (Glass fiber reinforced aluminum laminates) combines the advantages of both metal and composites (Mrzljak et al., 2020). GLARE laminates have been applied in some structural parts of civil aircrafts such as the fuselage skin of Airbus A380 (Guan et al., 2009) and the bulk cargo floor of Boeing B777 (Chai and Manikandan, 2014) due to good impact damage resistance, fatigue properties (Bhat and Patibandla, 2013), corrosion resistance (Wang, 2020), and anti-fire performance (Li et al., 2020). GLARE is fabricated by hot-pressing of alternate multi-layers of aluminum alloy sheet and unidirectional glass fiber/epoxy resin prepreg, the bonding strength of the interface determines interfacial stress transfer degree (Gonzalez-Canche et al., 2018) and has an obvious influence on the interlaminar as well as the comprehensive properties (Hu et al., 2020; Ji et al., 2020).…”
Section: Introductionmentioning
confidence: 99%